ANALISIS STRUKTUR BATIN DAN STRUKTUR FISIK PADA PUISI “IBU” KARYA D. ZAWAWI IMRON - Dendy Ginanjar; Fajar Kurnia; Nofianty Nofianty (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to (1) analyze the inner structure and physical structure of his poetry D. Zawawi Imron entitled "Ibu" (2) to describe the inner structure and physical structure of poetry. The method used is descriptive qualitative research method. This data analysis is done through several stages: literature study by reading, recording and identifying rice lines of poetry that belong to the inner structure and physical structure of poetry. From the results obtained the poem entitled "Ibu" by D. Zawawi Imron has several inner Structure consisting of theme, feeling, tone, atmosphere and mandate and physical structure of poetry such as diction, concrete word, image, majas, rima, and typography.